Enhancing the inpatient ward learning environment: A practical guide. (20th October 2021) - Carter, Adam Nicholas; Gifford, Albert; Lyons, Amy Victoria; Milton, Joseph Sebastian; Streeter, Hamish; Carter, Matthew
Abstract: Inpatient ward placements are rich with practical learning opportunities for medical students; however, many such opportunities go overlooked and underused. Newly qualified doctors often feel underprepared for work on wards; improving student experience on ward placements can address this. Although this requires an active effort from both students and clinical educators, it is not arduous and has mutual benefit: improving medical education while simultaneously reducing staff workload. Here, we present a guide for both teachers and students highlighting three key areas of ward learning that may be improved: strategies to drive active learning, integration of students into the ward team and underutilised resources to develop a patient‐centred approach.